The Use of Picture Story Media to Enhance Reading Interest of Third-Grade Students at UPT SD Negeri 1 Sereang - Nurlina; Suardi Zain; Nurzin R Kasau (INTERACTION: Jurnal Pendidikan Bahasa, 2026)
Reading interest among elementary school students remains a challenge, particularly when students are less enthusiastic about literacy activities and are more attracted to entertainment-based activities. This study investigated the effectiveness of picture stories in improving reading interest among third-grade students at UPT SD Negeri 1 Sereang. The study employed a quantitative approach using a one-group pre-test–post-test design. Data were collected through reading interest questionnaires, observation, and documentation. The treatment involved structured reading activities using picture stories for 10–15 minutes before learning activities, followed by discussion and sharing of story content. The findings indicated an improvement in students’ reading interest after the implementation of picture stories. The increase was reflected in students’ attention, participation, enthusiasm, and willingness to continue reading activities. The study concludes that picture stories are an effective instructional medium for supporting literacy development in elementary schools.